FACTORS AFFECTING THE PROFITABILITY OF MORINGA OLEIFERA PRODUCTION IN OYO STATE, NIGERIA - O., Ojo T.; S., Ogunleye A.; T., Alimi (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
This study identified the socioeconomic characteristics of Moringa oleifera farmers in Oyo State, estimated the costs and returns to M. oleifera production and determined the factors affecting the profitability of its production. This was with a view to providing information on how the production of M. oleifera could enhance the income of farmers. A multistage sampling technique was employed for this study. The data obtained were analysed with descriptive statistics, budgetary analysis and multiple regression technique. Major findings from the study showed that about 90% of the respondents were men thus, making moringa production a male dominant enterprise. The mean age of the farmers was 46.45 year and the average farming experience was 5.1 years. Literate farmers were predominant in the study area with the least being secondary education. The mean farm size was 1.77ha putting farmers into the class of smallholders. The study revealed that the level of education; planting materials; labour and land rent were the factors that affected the profitability of moringa farming and were statistically significant at 5% level. The profitability ratio gave a benefit-cost ratio of 2.77, this showed that M. oleifera production was profitable. The study concluded that M. oleifera farming is profitable and economically efficient in the study area. The study recommended that provision of improved planting material, access to labour and reduction in land rent could further enhance the profitability of moringa production.